Amygdala subnuclei volumes and anxiety behaviors in children and adolescents with autism spectrum disorder, attention deficit hyperactivity disorder, and obsessive–compulsive disorder. Issue 16 (12th July 2022) - Seguin, Diane; Pac, Sara; Wang, Jianan; Nicolson, Rob; Martinez‐Trujillo, Julio; Anagnostou, Evdokia; Lerch, Jason P.; Hammill, Christopher; Schachar, Russell; Crosbie, Jennifer; Kelley, Elizabeth; Ayub, Muhammad; et al.
Abstract: Alterations in the structural maturation of the amygdala subnuclei volumes are associated with anxiety behaviors in adults and children with neurodevelopmental and associated disorders. This study investigated the relationship between amygdala subnuclei volumes and anxiety in 233 children and adolescents (mean age = 11.02 years; standard deviation = 3.17) with autism spectrum disorder (ASD), attention deficit hyperactivity disorder (ADHD), and children with obsessive compulsive disorder (OCD), as well as typically developing (TD) children. Parents completed the Child Behavior Checklist (CBCL), and the children underwent structural MRI at 3 T. FreeSurfer software was used to automatically segment the amygdala subnuclei. A general linear model revealed that children and adolescents with ASD, ADHD, and OCD had higher anxiety scores compared to TD children ( p  < .001). A subsequent interaction analysis revealed that children with ASD (B = 0.09, p  < .0001) and children with OCD (B = 0.1, p  < .0001) who had high anxiety had larger right central nuclei volumes compared with TD children. Similar results were obtained for the right anterior amygdaloid area. Amygdala subnuclei volumes may be key to identifying children with neurodevelopmental disorders or those with OCD who are at high risk for anxiety. Findings may inform the development of targeted behavioral interventions to address anxiety behaviors and to assess the downstream effects of such interventions. Abstract : This study investigated the relationship between amygdala subnuclear volumes and anxiety in 233 children (mean age = 11 years; standard deviation = 3.17) with autism spectrum disorder (ASD), attention deficit hyperactivity disorder (ADHD) and children with obsessive compulsive disorder (OCD), as well as typically developing (TD) children. A general linear model revealed that children with ASD, ADHD, OCD had higher anxiety scores compared to TD children ( p  < .001) and a subsequent interaction analysis revealed that children with ASD (B = 0.09, p  < .0001) and children with OCD (B = 0.1, p  < .0001) with high anxiety had larger right central nuclei volumes compared with TD children. Amygdala subnuclei volumes may be key to identifying children with neurodevelopmental disorders at high risk for anxiety.